2023
DOI: 10.1186/s40478-023-01592-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the glycine-rich domain of TDP-43 with antibodies prevents its aggregation in vitro and reduces neurofilament levels in vivo

Abstract: Cytoplasmic aggregation and concomitant nuclear clearance of the RNA-binding protein TDP-43 are found in ~ 90% of cases of amyotrophic lateral sclerosis and ~ 45% of patients living with frontotemporal lobar degeneration, but no disease-modifying therapy is available. Antibody therapy targeting other aggregating proteins associated with neurodegenerative disorders has shown beneficial effects in animal models and clinical trials. The most effective epitopes for safe antibody therapy targeting TDP-43 are unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Together these results provide important proof-of-concept evidence for non-invasive, FUS +MBfacilitated antibody transport across the in vitro ALS BBB, which could aid in improving the delivery of large molecule drugs and TDP-43-directed immunotherapies (96)(97)(98)(99) in ALS. With no such platform reported to date, our study provides the first patient-cell-derived model for investigation of FUS +MB bioeffects and screening of FUS +MB -deliverable drug formats most compatible with disease subtypes, supporting personalised medicine approaches to ALS drug delivery.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Together these results provide important proof-of-concept evidence for non-invasive, FUS +MBfacilitated antibody transport across the in vitro ALS BBB, which could aid in improving the delivery of large molecule drugs and TDP-43-directed immunotherapies (96)(97)(98)(99) in ALS. With no such platform reported to date, our study provides the first patient-cell-derived model for investigation of FUS +MB bioeffects and screening of FUS +MB -deliverable drug formats most compatible with disease subtypes, supporting personalised medicine approaches to ALS drug delivery.…”
Section: Discussionmentioning
confidence: 67%
“…With BBB limiting an estimated 99.8 % of peripherally administered large molecule drugs such as therapeutics antibodies (95), we next tested the possibility of enhancing the permeabilisation of ALS BBB to large molecules with FUS +MB . As a proof-of-concept, we trialled the delivery of anti-TDP-43 antibody, considering promising preclinical development of TDP-43 targeted immunotherapies (96)(97)(98)(99) as well as the recent clinical success of therapeutic antibodies in the treatment of other neurodegenerative disorders (100)(101)(102)(103)(104). Although the utilised anti-TDP-43 antibody has not yet proved therapeutically beneficial, we were previously successful in delivering Aducanumab (Aduhelm TM ) and anti-tau therapeutic antibodies with FUS +MB in human Alzheimer's disease in vitro models (37,41); and a recent clinical study demonstrated beneficial effects of Aducanumab combined with FUS +MB in Alzheimer's disease patients, as compared to Aducanumab alone (104).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, immunotherapy using mAbs to target misfolded proteins has been widely investigated to treat neurodegenerative diseases. In fact, it has recently been reported that immunization with pS409/410-TDP-43 peptides, as a passive immunotherapy approach, reduces neuroaxonal damage in a TDP-43 mouse model [ 27 ]. We therefore believe our antibodies have therapeutic potential for the treatment of FTD/ALS and other TDP-43 proteinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…For the other approach, we used a 1:100 dilution of the recombinant monoclonal guinea pig Iba1 antibody from Synaptic Systems (catalog no. 234 308, Göttingen, Germany) against the allograft inflammatory factor 1 in the cytoplasm of the microglia (Glotfelty et al 2023 ; Riemenschneider et al 2023 ). To detect the primary antibody binding, we used an Alexa 488-coupled secondary antibody from Invitrogen (A11034 and A11073, Darmstadt, Germany) matching the species of the primary antibodies.…”
Section: Methodsmentioning
confidence: 99%